Insulin Resistance in Patients With Acromegaly - Vila, Greisa; Jørgensen, Jens Otto L.; Luger, Anton; Stalla, Günter K. (Frontiers in Endocrinology, 2019)
Acromegaly is characterized by chronic overproduction of growth hormone (GH) that leads to insulin resistance, glucose intolerance and, ultimately, diabetes. The GH-induced sustained stimulation of lipolysis plays a major role not only in the development of insulin resistance and prediabetes/diabetes, but also in the reduction of lipid accumulation, making acromegaly a unique case of severe insulin resistance in the presence of reduced body fat. In the present review, we elucidate the effects of GH hypersecretion on metabolic organs, describing the pathophysiology of impaired glucose tolerance in acromegaly, as well as the impact of acromegaly-specific therapies on glucose metabolism. In addition, we highlight the role of insulin resistance in the development of acromegaly-associated complications such as hypertension, cardiac disease, sleep apnea, polycystic ovaries, bone disease and cancer. Taken together, insulin resistance is an important metabolic hallmark of acromegaly, which is strongly related to disease activity, the development of comorbidities, and might even impact the response to drugs used in the treatment of acromegaly.